PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 004 TELUK PULAU HILIR KECAMATAN RIMBA MELINTANG - Masni Tambunan; Zetra Hainun Putra; Hendri Mahardi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem in this research is the low of students’ result because the teacher still uses conventional teaching model, so that the students get pasif and less motivation. The students are less understanding to the concept that is studied, so that student often can not answer the question given by teacher in the end of the lesson. Because of that, researchers apply inquiry learning model. Method using in this research is classroom action research that is done at SDN 004 Teluk Pulau Hilir. Subject in this study is 20 students of grade V. The based score of students’ result is 66, increases into 70,25 in the first cycle, and raise at cycle II become 76,75. The progress of students’s results is showed by the increase of persentase of teacher’s and students’ activities. Teacher’s activity at cylce I is namely 59% and at cyles II is namely 79%. Persentation of student’s activity at cycle I is namely 59,17% and at cycle II accros progress is namely 77,40%. Finally it can be concluded that inquiry learning model can increase science learning result of grade IV SD Negeri 004 Teluk Pulau Hilir, Rimba Melintang Rokan Hilir.Keywords: Inquiry Learning Model, Science Learning Result